Multi-fractal structure features of corn stalks and their correlation with pretreatment homogeneity and efficacy. (February 2022) - Sui, Wenjie; Zhou, Xiaodan; Su, Hao; Wang, Guanhua; Jiang, Wei; Liu, Rui; Wu, Tao; Wang, Shuai; Jin, Yan; Zhang, Min
Highlights: Multi-fractal structure features of steam exploded corn stalks were characterized. Fractal features on different scales had same variation trend with treatment severity. Low surface fractal dimension correlated to high pretreatment homogeneity. Decrease in pore fractal dimension corresponded to increased pretreatment efficacy. Negatively linear tendency was found in fractal dimensions vs solid digestibility. Abstract: Lignocellulose biomass is a natural porous medium with fractal characteristics, which tend to be distinct after certain pretreatment and relational with processing effects. In this work, multi-scale fractal features of corn stalks after steam explosion pretreatment were systematically characterized employing digital image processing and mercury intrusion porosimetry methodologies. The macroscopic surface fractal features ( Ds : 2.8278 ∼ 2.8523) and microscopic pore fractal features ( Dp : 2.3003 ∼ 2.8867) presented same variation tendency with pretreatment severity, revealing the self-similarity of processing results of corn stalks with the scale. In association with pretreatment homogeneity and efficacy, the decrease in fractal dimensions corresponded to morphologically homogeneous and structurally complex samples with preferable auto-hydrolysis degree of structural components, which led to high reactivity with enzymes. Quantitatively, there were strongly linear correlation between fractal dimensions and enzymatic digestibility with r 2 > 0.95. Fractal dimension was expected to theoretically guide the rational evaluation, prediction and promotion of the key pretreatment technique in biorefinery.